Two-Dimensional Continuous Model for Bacterial Flows through Microfluidic Channels - Figueroa-Morales, Nuris; Altshuler, Ernesto; Hernández-García, A.; Lage-Castellanos, Alejandro; Clément, Eric (Revista Cubana de Física; Vol 30 No 1 (2013), 2013)
Dispersion and migration of bacteria under flow in confined structures is related to a large spectrum of practical interests, and lacks a fully satisfactory understanding. We introduce a simple bidimensional continuous model trying to describe the main characteristics of the movement of E. colialong a microchannel. Their convective transport, lateral wall absorption/desorption processes and migration along lateral walls are taken into account. The model reproduces the anomalous dispersion of bacteria when passing through a constriction.